Staff shortages in critical care units: Critical care nurses experiences - Monika Nakweenda; Ramona Anthonie; Mariana van der Heever (International Journal of Africa Nursing Sciences, 2022)
Introduction: The nursing activities in critical care units globally and in Namibia are influenced by a shortage of critical care nurses. This shortage led to hospitals resorting to a variety of staffing strategies such as a team nursing model, variable staffing, the use of agency nurses and float staff to achieve the recommended nurse to ratio of 1:1 or 1:2. Aim: The purpose of the study was to explore the experiences of critical care nurses regarding staff shortages in critical care units. Methods: A descriptive qualitative design was applied. Purposive sampling was used to select a sample from a total population of 18 critical care nurses. Data saturation was reached by the 11th participant, leading to a final sample of 11. Data were collected through individual interviews using a semi-structured interview guide. Data were analysed manually using the approach described by Creswell and Creswell (2018). Findings: Six themes emerged from the data analysis, i.e., critical care work environment, quality of care, workforce planning, staffing strategies, job satisfaction and continuous professional development. Findings from the study revealed that participants worked with an increased nurse to patient ratio that consequently influenced the quality of care rendered to patients. Conclusion: The staff shortages influenced the number of patients that was assigned per nurse. Accordingly, each nurse had to care for more than two patients. The subsequent increased workload influenced the provision of quality nursing care.